Temporomandibular joint disorder and cervical spine pain a retrospective study - Elefano, Vie Monique C.; Palanca, Sharon Mary Q.; Boncan, Ricardo B. (Adviser).
A controversy exists on whether pain felt along the cervical spine (i.e., at the neck, shoulder and upper back region), is associated with temporomandibular joint disorder (TMD). The purpose of this study is to determine if there is a relationship between the signs and symptoms of TMD and pain along the cervical spine. A group of 155 patients was systematically selected out of 345 patients from the study population whose ages range from 18-45 years old. Records were examined using a checklist about pain and accompanying signs and symptoms. Results from data analysis using the chi square test did not reach significance. However, raw data presented a significantly greater number of patients suffering from both. This study therefore showed that although there is no strong relationship between signs and symptoms of TMD and pain at the cervical area, a possibility of overlapping signs and symptoms may exist in the two regions because of their anatomical proximity and physiological similarities.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.